STUDENTS' ABILITY IN PRONOUNCING ENGLISH FRICATIVE CONSONANTS AT ENGLISH LANGUAGE EDUCATION OF FKIP UIR - Maysarah; Andi Idayani; Betty Sailun (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2023)
This research aims to know the students' ability to pronounce English Fricative consonants at English Language Education of FKIP UIR. The design of this research is descriptive research with a qualitative approach. The researcher conducted the study at English Education of FKIP UIR. The researcher took 30 students from 65 second-semester students' at English Education of FKIP UIR. In this research, the researcher used the purposive sampling technique. The research instrument is a pronunciation test consisting of 26 words, and a recorder collected the data. The online Cambridge-American dictionary is used as the correction standard by the researcher. The result of data analysis showed that the average score for students' pronunciation was 19,62, with scores ranging from 7.4. Afterward, the findings revealed that students still have many problems pronouncing English fricatives, especially in /f/, /θ/, and /ʒ/ sounds. Meanwhile, the researcher found the most trouble when students were pronouncing the fricative sound /ʒ/ in the initial position. After that, the sound /f/ in the medial and /ʒ/ in the final position have the same lower score. Then, there is a problem when students pronounce the /θ/ sound and the/ sound in the final position. In conclusion, the student's ability to pronounce English fricative consonants at FKIP UIR English Language Education is fairly good.